Measurement of the decay rate of the radiative K-e3(0) decay - Leber, F; Beier, T; Blumer, H; Coward, D; Kleinknecht, K; Renk, B; Sander, H; Scheerer, F; Scheidt, J; Staeck, J; Wagner, A; Barr, G; et al. (1996)
Data from the NA31 experiment at CERN have been used to measure the decay KL → π±e∓vy (K0e3γ). 1384 ± 53 events of this decay type have been observed. The decay rate relative to K0e3 is found to be Γ(K0e3γ, E(Black star)γ ≥ 30 MeV, Θ(Black star)e-γ ≥ 20°)/Γ(K0e3) = (0.934 ± 0.036 (stat.) +0.055-0.039 (syst.))% which corresponds to a branching ratio of BR(K0e3γ, E(Black star)γ ≥ 30 MeV, Θ(Black star)e-γ ≥ 20°) = (0.361 ± 0.014(stat.) +0.021-0.015 (syst.))%. The result is in good agreement with theoretical predictions. The decay KL → π±e∓vγ is found to be dominated by internal bremsstrahlung.